The TPACK Framework in English Language Education Practice: A Bibliometric Analysis - Humaera, Isna; Salija, Kisman; Amin, Fatimah Hidayahni; Sakkir, Geminastiti; Nasrullah, Nasrullah; Ramdani, Amaliah (The Eastasouth Journal of Learning and Educations, 2025)
The Technological Pedagogical and Content Knowledge (TPACK) framework has emerged as a central framework for technology integration in English language education. This study conducts a bibliometric analysis of the research literature on TPACK in English language education (ELT) to examine publication trends, citation patterns, thematic clusters, and collaboration networks. The findings demonstrate steady interest in research, with intense acceleration during the digital shift precipitated by the COVID-19 pandemic. Some of the developing themes identified are teacher education, e-learning integration, and subject-area-specific applications. The research identifies both the benefits and challenges of TPACK implementation, demanding large-scale instructor training and organizational support. Longitudinal studies and the use of new technologies such as artificial intelligence and virtual reality in TPACK-based teaching approaches should be the subject of future studies.